Analisis Bibliometrik tentang Distribusi Vaksin Covid-19 Tahun 2020-2021 - Kusumawati, Desi; Perwitasari, Dyah Aryani; Supadmi, Woro Woro Supadmi (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Covid-19 is an infectious disease that has caused the highest mortality since 2019. This study aims to determine the map of research developments related to ‘Covid-19 Vaccines’. This article review was conducted by searching for publications through the Pubmed database in October-November 2021 with the keyword ‘Vaccines/supply and distribution’. The publication map in this study researchers used bibliometric analysis of the Biblioshiny web interface application for the article search period during 1 January 2020 - 30 November 2021 in Pubmed found around 6528 articles. The article that ranked first out of 1406 articles was The New Englands Journal Of Medicine with 214 articles (15.22%), Vaccine with 208 articles (14.79%), and Nature with 189 articles (13.44%). The most authors out of 444 authors were Baden LR with 63 articles (14.19%), Rubin Ej with 57 articles (12.84%) and Morrisey S with 56 articles (12.61%). Institutions or institutions dominated by European-American origin ranked first University Of Oxford with 1229 articles (29.57%), followed by Harvard Medical School with 484 articles (11.65%), followed by the National Institute Of Allergy And Infectious Diseases with 376 articles (9.05%). The most keywords in Pubmed searches in the period during the study were related to Covid-19 Vaccine/supply & distribution in a table showing keywords with the word Human had a frequency of use of 6432 times (98.52%) then keywords with the word sars-cov-2 had been used 3275 times (50.2%) then the 3rd highest was keywords with the word covid-19 vaccines had been used 3268 times (50.1%) of the total number of articles available. Author productivity is mostly dominated by European countries, namely Argentina and Afghanistan.